UHPLC-Q-Orbitrap HRMS and network analysis to explore the mechanisms of QiShenYiQi dripping pill for treating myocardial infarction - Liu, Zhichao; Fu, Huanjie; Gan, Yongkang; Ye, Yujia; Huang, Binghui; Jiang, Mingxiu; Chen, Jinhong; Li, Xiaofeng (Frontiers in Pharmacology, 2024)
This study focused on examining the protection of QiShenYiQi dripping pills (QSYQ) against myocardial infarction (MI) and investigating its potential mechanisms. Ultra high performance liquid chromatography-q exactive-orbitrap high resolution mass spectrometry (UHPLC-Q-Orbitrap HRMS) was employed to analyze potential active compounds of QSYQ. The targets of these compounds were predicted using an integrated in silico method and cross-referenced with relevant databases to identify associated pathways. Experimental validation was then conducted to confirm the accuracy of the systems pharmacology findings. In the end, network analysis combined with UHPLC screened 13 potential active compounds and obtained 99 targets for the intersection of potential active compounds and diseases. The enrichment analysis results indicated that the cyclic guanosine monophosphateprotein kinase G (cGMP-PKG) signaling pathway might be the mechanism of action of QSYQ in the treatment of MI. Experimental verification demonstrated that QSYQ could alleviate oxidative stress, promote vasodilation, and activate proteins related to the mitochondrial ATP-sensitive potassium channel (KATP) and nitric oxide (NO)-cGMP-PKG signaling pathway. This study provides insights into both the pathogenic mechanisms underlying MI and the molecular mechanisms through which QSYQ may confer protection. Given the role of PKG in regulating myocardial stiffness, it emerges as a promising therapeutic target for myocardial remodeling. We propose that the NO-cGMP-PKG and mitochondrial KATP pathways may serve as candidate therapeutic targets for the development of new interventions for MI.